MILIARIA - Tgk. Fikri Ardiansyah; Wizar Putri Mellaratna (Lembaga Pengembangan Kinerja Dosen, 2024)
Prickly heat is also known as heat rash or miliaria which is a skin problem caused by blockage of the sweat glands. Usually they look like small pink bumps, feel itchy or feel prickly. Prickly heat occurs due to blockage of the sweat glands caused by Staphylococcus epidermidis bacteria, this bacteria produces extracellular polysaccharide substance (EPS). Prickly heat does not only occur in babies and children, but can also occur in adults. In adults, prickly heat usually occurs in the folds of the skin or parts of the skin that often rub against clothing. Meanwhile, prickly heat in babies often occurs on the neck, shoulders, chest, armpits, elbow creases and thighs. The diagnosis of miliaria is made based on sufficient clinical manifestations or images. The goal of treatment for miliaria is to eliminate symptoms and prevent hyperpyrexia and heat exhaustion symptoms. Thus, you must avoid things that cause blockage of the openings of the eccrine sweat glands.